2015
DOI: 10.1371/journal.pone.0139102
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Pathologic Air Trapping in Lung Transplant Patients Using CT Density Mapping: Comparison with Other CT Air Trapping Measures

Abstract: To determine whether density mapping (DM) is more accurate for detection and quantification of pathologic air trapping (pAT) in patients after lung transplantation compared to other CT air trapping measures. One-hundred forty-seven lung and heart-lung transplant recipients underwent CT-examinations at functional residual capacity (FRC) and total lung capacity (TLC) and PFT six months after lung transplantation. Quantification of air trapping was performed with the threshold-based method in expiration (EXP), de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 29 publications
(54 reference statements)
0
25
0
Order By: Relevance
“…It has been reported that expiratory CT can detect air trapping which is frequently observed in obstructive change. 18 - 21 Therefore, I/E CT volumetry was able to detect not only restrictive change but also obstructive change. In BOS patients, inspiratory lung volume was gradually increased, and expiratory lung volume was also increased by emphysematous change.…”
Section: Discussionmentioning
confidence: 97%
“…It has been reported that expiratory CT can detect air trapping which is frequently observed in obstructive change. 18 - 21 Therefore, I/E CT volumetry was able to detect not only restrictive change but also obstructive change. In BOS patients, inspiratory lung volume was gradually increased, and expiratory lung volume was also increased by emphysematous change.…”
Section: Discussionmentioning
confidence: 97%
“…There were several limitations in this study. First, we did not have routine expiratory CT performed at the time of the inspiratory CT; therefore, we could not assess air‐trapping, which could have been a useful parameter to assess patient survival for BOS. In addition, we evaluated only the lungs and we did not analyze the density changes in the pleura, which could be a useful factor for RAS patients .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Solyanik et al compared 3 methods of quantifying air trapping in LTx patients (18). Their approach differed from the present study in that multiple measurements within the same patients were not obtained.…”
Section: Discussionmentioning
confidence: 99%